Les chapiteaux antiques remployés dans la mosquée de Bou Merouane (Algérie) : essai de datation et de recontextualisation - Sara Imène Boumaraf; Redha Attoui; Mariette de Vos Raaijmakers (Antiquités Africaines)
The remains of the ancient city of Hippo Regius indicate significant construction activity near the sea, within a characteristic architectural ensemble built from the local materials. The marble from the nearby quarries of Cap de Garde was used for carving columns and various types of capitals. George Marçais noted that numerous capitals were transferred from ancient Hippo Regius in 1033 AD to be reused in the construction of the Bou Merouane Mosque in Bûna (Annaba, Algeria). The documentation of the excavations in the region of Hippo Regius, carried out during the French colonization of Algeria after 1830, do not allow us to suggest the exact provenance of the capitals of the ancient city, and those of the Bou Merouane Mosque.